Επισκευάζοντας τα τείχη της Κωνσταντινούπολης: αυτοκρατορικές πρωτοβουλίες κατά την ύστερη βυζαντινή περίοδο - ΑΘΑΝΑΣΟΠΟΥΛΟΣ Αντώνης (Byzantina Symmeikta, 2017)
Repairing the walls of Constantinople: Emperors’ initiatives during the late byzantine period The aim of this study is to present the initiatives of the late Byzantine period emperors regarding repairs, reconstruction or reinforcement of the fortification walls of Constantinople. These initiatives are examined in the context of the particular circumstances of each period, i.e. when external enemies were threatening the Byzantine capital or when the imperial treasury was impoverished, a problem which almost all the emperors of the period in question faced and which inevitably was, for each one of them, a constraint in implementing a complete wall-repairing plan. The repairs to the walls were mostly occasional: they would be done when need arose and according to the funding available. However, even until the first quarter of the 15th century, the walls could protect effectively Constantinople against the aspirant conquerors. The balance changed with the emergence and evolution of firearms and their widespread use by the Ottomans. The agony of the residents concerning the strength of the walls was widespread, as recorded in historiographical texts of the time, orations, etc. The ambitious efforts of John VIII to undertake an extensive restoration program for the walls in the years 1433-1444, with the financial support of private sources, was a last attempt of defense against a superior enemy.